2016
DOI: 10.1155/2016/3658013
|View full text |Cite
|
Sign up to set email alerts
|

Stem/Progenitor Cell Niches Involved in Hepatic and Biliary Regeneration

Abstract: Niches containing stem/progenitor cells are present in different anatomical locations along the human biliary tree and within liver acini. The most primitive stem/progenitors, biliary tree stem/progenitor cells (BTSCs), reside within peribiliary glands located throughout large extrahepatic and intrahepatic bile ducts. BTSCs are multipotent and can differentiate towards hepatic and pancreatic cell fates. These niches' matrix chemistry and other characteristics are undefined. Canals of Hering (bile ductules) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 115 publications
2
81
0
Order By: Relevance
“…28 The structures we have reported are very similar to structures recently reviewed in a report that focused on the hepatic niche and the presence of Hepatic Stem Cells (HpSCs) in "reactive ductules." 28 In Fig. 4A of that report, HpSCs that are CK7+ and Sox9+ are identified at the edge of reactive ductules.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…28 The structures we have reported are very similar to structures recently reviewed in a report that focused on the hepatic niche and the presence of Hepatic Stem Cells (HpSCs) in "reactive ductules." 28 In Fig. 4A of that report, HpSCs that are CK7+ and Sox9+ are identified at the edge of reactive ductules.…”
Section: Discussionsupporting
confidence: 76%
“…In a recent review, 28 the liver stem cell niche is examined in great detail, and structures are identified in severely diseased livers that greatly resemble those in this report. Two markers of stem progenitor cells that were reviewed and identified in ductular structures in the diseased livers were CK7 and Sox-9.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…HOCs are bipotent and able to further mature to hepatocytes or cholangiocytes when there is injury causing loss of hepatocytes or cholangiocytes, especially under a condition in which hepatocellular proliferation is inhibited, 25 and so do small hepatocyte-like cells in a scenario of pre-treatment with retrorsine before partial hepatectomy. 26 One study indicated that bone morrow cells may migrate into injured liver to become the source of oval cells. 27 In human liver, ductular epithelial cells, 28 or primitive hepatic stem cells 29 and EpCAM-positive cells are believed in a progenitor cell compartment.…”
Section: Discussionmentioning
confidence: 99%
“…HPCs minimally contribute to the normal turnover of liver parenchymal cells but are activated in the context of liver injuries [103]. The activation of HPCs is sustained by a specialized niche that furnishes several key signals driving HPC activity [104]. In normal conditions, HPCs are surrounded by endothelial cells, HSCs, and KCs, which release paracrine signals for the maintenance of the stem/progenitors in a quiescent state.…”
Section: Liver Tissue Inflammationmentioning
confidence: 99%